Facile fabrication of mesoporous photoanodes for dye-sensitized solar cells by microwave sintering of binder-free TiO2 paste - Kim, Sang Yong; Ryu, Shin Young; Ha, Na Young; Ahn, Y. H.; Park, Ji Yong; Lee, Soonil (Journal of Physics D: Applied Physics, 2018)
We report that microwave (MW) treatment of binder-free TiO2 paste coating is a facile method that can replace energy- and time-consuming high-temperature sintering processes in the production of mesoporous electrodes in dye-sensitized solar cells. For example, 5 min of MW treatment at 110 W is sufficient to produce a device with ∼4% efficiency. Conventional sintering at 375 or 450 °C for ∼2 h is required to make devices with a comparable efficiency. Compatibility with common plastic substrates is another advantage of MW-treatment process. Substrate temperature remained below 205 °C after 5 min of MW treatment. Analysis of impedance spectra using equivalent circuit model showed a correlation between device performance and resistances. Specifically, the sum of charge-transfer resistances at TiO2-TiO2 and Pt-electrolyte junctions, the Warburg component, and contact and FTO sheet resistances was in good agreement with the series resistance deduced from the fitting of measured J-V curves to an imperfect diode with parasitic resistances. Moreover, the discrepancy in variations of short-circuit current and charge-transfer resistance in TiO2 electrodes indicated that MW sintering can be effective in reducing charge-transfer resistance without sacrificing dye adsorption.
Keywords: Binder free; Charge transfer resistance; Conventional sintering; Equivalent circuit model; High-temperature sintering; Impedance spectroscopy; Mesoporous TiO2; Microwave sintering; binder-free paste; dye-sensitizes solar cell; impedance spectroscopy; mesoporous TiO2 electrode; microwave sintering